ASSESSMENT OF COASTAL LAND USE CHANGES IN BANTEN BAY, INDONESIA USING DIFFERENT CHANGE DETECTION METHODS - PUVADOL DOYDEE; VlNCENTIUS SlREGAR (BIOTROPIA, 2006)
Many types of the coastal land use in Banten Bay have been assessed in order to know the change as evidently detected by Landsat imagery in 1994 and 2001. Image processing such as, supervised classification and various change detection techniques are performed to the satellite images. Red Green method showed the best result for detecting the coastal land use change. This method is suitable for detecting the increasing areas of the paddy fields and settlement. Image Differencing method is capable to detect the increasing areas in agriculture, decreasing in fishponds and natural areas. Image Ratioing method can be considered suitable for detecting the increasing area of fishponds, decreasing of paddy fields and agriculture areas. Each coastal land use type has increased, except for the natural area/brushwood. Most of agriculture and paddy fields areas have been converted to fish ponds. Key words: coastal land use/land cover, change detection method, remote sensing